Characterization of SARS-CoV-2 isolated from a patient in Iran compared to SARS-CoV-2 different variants. Issue 4 (4th March 2023) - Ahmadi, Khadijeh; Hosseinpour, Mahmood; Rismani, Elham; Hassaniazad, Mehdi; Mafakher, Ladan; Jahantigh, Hamid Reza; Eftekhar, Ebrahim; Gouklani, Hamed
Abstract: Since the onset of the global epidemic of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS‐CoV‐2), whole genome sequencing of virus in all countries has been considered to track and predict virus transmission and variation patterns. In the current study we reported a novel complete genome sequence of SARS-CoV-2 isolated from Iran. Genomics variations and protein sequences were evaluated for the isolated sequence and seven Iranian complete genome sequences of SARS-CoV-2 from NCBI using the reference genome of the SARS-CoV-2 Wuhan-Hu-1. The results showed six nucleotide substitutions. The multiple sequence alignment of the spike protein of the Wuhan-Hu-1 strain and the emerging variants indicated similar its residue pattern in the current sequence to the Wuhan-Hu-1 strain. There were relatively similar binding affinity and residues involved in the interactions of the spike receptor-binding domain (RBD) of the Wuhan-Hu-1 strain, the variants and Hormozgan With angiotensin-converting enzyme 2 (ACE2). Tracing the phylogeny of virus indicated distinct clustering of Iranian variants in branches close to the Asian countries. The mutation effect study on the function of proteins predicted neutral impact of all six nucleotide substitutions. However, the free energy calculations indicated a decreasing the protein stability related to the mutations. This data, consistent with similar studies, showed that despite the high similarity in the nucleotide sequence of the SARS-CoV-2, the mutation pattern varies from country to country. Therefore, any country can benefit from these studies to track and find appropriate strategies for treating and controlling the epidemic. Communicated by Ramaswamy H. Sarma